PENGEMBANGAN PLUGIN LAPORAN PENJUALAN PADA TOKO BIBIT BEBEK BERBOBOT BERBASIS WORDPRESS - Estu Ramadian Wiharto; Astria Hijriani; Rizky Prabowo (Jurnal Pepadun, 2021)
The rapid growth of e-commerce encouraging the trend of store digitization. All popular e-commerce provider prohibit the sale of living goods. It makes the livestock industry like Bibit Bebek Berbobot Store unable to digitize like most shops. WordPress is a multipurpose CMS. WordPress can be used to build selling system to substitute popular e-commerce. WordPress has many features, such as plugins and a template system. Plugins are provided to improve and add functions that do not exist in a website. With a plugin called WooCommerce, WordPress can be transformed into a selling system. WooCommerce add several features such as ordering, product management, and stock management, but it is still lack proper reporting feature. This research focus on developing a plugin that allows processing transaction data into monthly accounting reports. Plugin development is carried out using the PHP programming language with the waterfall development method. The final product of this plugin is monthly accounting reports such as sales journals, inventory journals, and income reports